DIPLOMACY, HISTORY AND ETHICS: A PHILOSOPHICAL ANALYSIS OF EUROPEAN, AMERICAN AND GEORGIAN DIPLOMATIC PRACTICE - Madona Kebadze; Giorgi Sibashvili (The Conference Hub, 2025)
Diplomacy is not merely a political or administrative process; it represents a synthesis of history, ethics, and moral responsibility. This paper examines examples from the modern and contemporary histories of European and American countries, as well as from Georgian diplomatic experience, and integrates them within a philosophical framework. It demonstrates how diplomatic decisions can be interpreted not only through factual or pragmatic dimensions, but also through ethical and moral perspectives. The study argues that diplomatic practice constitutes a form of ethical action in which historical experience, legal responsibility, and philosophical-moral synthesis are interconnected.
Keywords: Diplomacy, history, ethics, moral responsibility, philosophy, Europe, America, Georgia.